A Band-Notched Antenna With Two Radiation Zeros Using Grounded Coplanar Waveguide Filter for 2.4/5 GHz WLAN Applications - Li, Min; Xu, Feng (Frontiers in Physics, 2021)
In this paper, a band-notched dual-polarized crossed dipole antenna is proposed for 2.4/5 GHz WLAN applications. The proposed antenna works on the WLAN 2.4-GHz (2.4-2.48 GHz) and 5-GHz (5.15-5.85 GHz) bands for VSWR < 2 with two radiation zeros within 3.4-3.6 GHz. Firstly, an ultra-wideband crossed dipole antenna with operating frequency of 2.4-5.8 GHz is designed using the grounded coplanar waveguide (GCPW) feeding structure. Secondly, a miniaturized defected microstrip structure (DMS) is embedded in the GCPW feeding strip to form a stopband behavior with a radiation zero. Finally, combining with the design of C-shaped split ring resonator (SRR) on the arms of dipole antenna, a band-notch (3.4-3.6 GHz) with two radiation zeros can be realized. These two radiation zeros can be adjusted independently to achieve wide stopband performance. As a result, compared with the original ultra-wideband dipole antenna, the realized gains of the proposed antenna in the 3.4-3.6 GHz range are all suppressed from 8 dBi to less than -8 dBi. The proposed antenna can realize stable unidirectional radiation pattern and high gain of around 7 dBi in lower band and 8.5 dBi in higher band of WLAN. As a demonstration, the proposed antenna is fabricated and measured, and the measurement results are in good agreement with the simulation results.